Relevance of 5A’s in tourism: A case study at 3 destinations in Karnataka - Sunil, Devu; P, Akshay M.; S, Ekanath; K, Arun (International Journal of Psychosocial Rehabilitation, 2020)
Over the years, one of the major economic activities that have developed significantly is tourism - both in developed and developing countries. People move from one place to another for exploring and enjoying the beauty of places. This paper looks into the basic infrastructure facility at tourist destinations of Karnataka in India, by making use of ‘5As’. Earlier people used to travel by sea routes, though they are affordable and convenient it was time seeking. Also the people were not having enough information in- hand, ahead of the travel to a particular destination. Technology advancement changed the whole scenario and now people make a thorough study of a particular destination well ahead of their travel and do their planning accordingly. Usually a tourist does so by looking into five basic aspects – attractions, accessibility, accommodation, activities, and amenities. Thus people can travel easily and safely without wasting any time anywhere in the world, more conveniently and comfortably.